Keputusan Memilih Perguruan Tinggi Ditinjau dari Personal Selling, Citra Merek, dan Kepercayaan Merek sebagai Variabel Intervening - Adelina Lubis; Ihsan Effendi; Nasib Nasib; Manda Dwipayahi Bhastary; Ahmad Fadli (Society, 2023)
In pursuing enhancing human resources’ quality, the state has ensured that private universities also have rights and obligations. The main objective of this study is to investigate whether personal selling and brand image influence college decision-making through the mediating role of brand trust. This research was conducted at the Politeknik Unggul LP3M in Medan, Indonesia. The study’s population was comprised of active students from the 2019/2020 academic year, totaling 257 individuals. A stratified sampling technique was employed, using the Slovin formula with a 5% margin of error, resulting in a sample size of 157 respondents. The study utilized a quantitative approach, with data collected through structured questionnaires. The analysis included descriptive statistics, reliability tests, and path analysis to determine the direct and indirect effects of personal selling and brand image on college decision-making through brand trust. The findings indicate that personal selling significantly affects brand trust, suggesting that effective strategies can enhance students’ trust in the institution’s brand. Similarly, brand image significantly directly affects brand trust, underscoring the importance of a positive brand image in building trust among potential students. Furthermore, the results show that personal selling indirectly influences college decision-making through brand trust, indicating that the trust developed through personal selling efforts can lead to positive college choice decisions. Likewise, brand image indirectly affects college decision-making through brand trust, highlighting the role of a strong brand image in shaping students’ enrollment decisions. In conclusion, personal selling and brand image are crucial in influencing college decisions, with brand trust as a key mediating variable. These findings provide valuable insights for educational institutions aiming to enhance their marketing strategies and build stronger relationships with prospective students. Future research could explore additional factors influencing college decision-making and examine these relationships in different educational contexts.